Microwave-Assisted Flow Chemistry for Green Synthesis and Other Applications - Mooney, Tara; Ilamanova, Maysa; Török, Béla (Current Microwave Chemistry, 2022)
Using combined microwave-assisted flow chemistry approaches is one of the most active areas of microwave chemistry and green synthesis. Microwave-assisted organic synthesis (MAOS) has contributed significantly to developing green synthetic methods, while flow chemistry applications are quite popular in industrial chemistry. The combination of the two has farreaching advantages. In early studies, the flow chemistry concept was applied in domestic microwave ovens already indicating strong potential for future applications. The relatively small diameter of the flow reactors can address the limited penetration depth of microwaves, which is a major impediment in large-scale batch reactors. With the commercial availability of dedicated microwave synthesizers with tunable frequencies and better temperature control, the possibilities to apply flow synthesis grew even broader. The developments focus on several issues; the two major ones are the design and application of reactors and catalysts. Common reactor types include microwave- absorbing, such as silicon carbide, and microwave-transparent materials, such as borosilicate glass, quartz, or Teflon, with the catalyst or solvent adjusted accordingly. Several heterogeneous catalysts are considered strong microwave absorbers that can heat the reaction from inside the reactor. Such materials include clays, zeolites, or supported metal catalysts. Here, the major advances in design and applications and the benefits gained will be illustrated by synthesizing fine chemicals, from organic compounds to nanoparticles and new materials.
Keywords: nanoparticles